Improving student’s learning outcomes and student’s activity of social science (IPS) subject by using jigsaw learning model at class VIII B in SMPN 14 sijunjung - Wildawati Wildawati; Azwar Ananda; Helmi Hasan (Jurnal Aplikasi IPTEK Indonesia, 2018)
This research aim to increase the learning on subject integrated and to increase the activities students’ results on subjects Integrated Social Science by using jigsaw learning model at B eigth class of SMPN 14 Sijunjung. This recearch used Action Recearch Approach. The subject of recearch was the students of B eigth class of SMPN 14 Sijunjung. The procedure of Action Recearch Approach concisted of three cycles in which each of it concisted of four stages: planning, action/implementation, observation, and reflection. The recearch instrumens were observation sheets, notes worksheet, tesis and dokumentation.  The data validity check was done by discussing with the expert of observers and corrector. The data was analyzed qualitatively and quantitatively.The result of the of recearch found that 1) the students result had increased which could be seen from the average score of examination after cycle that were cycle I, cycle II, and cycle III. This score had reached the expected indicators, that is or reached the criteria. 2) The learning activitiese of the B eight class studens on subjects Integrated Social Science by using jigsaw learning model had increased that was the activities score of cycle, cycle II, and cycle III. Based on the finding of the research it was concluded that the use of jigsaw learning model could increase the activities and the learning results of the students at B eight class of SMPN 14 Sijunjung on subjects Integrated Social Science.